The inherent challenges in creative musical performance in a paediatric hospital setting. (September 2013) - Preti, Costanza; Welch, Graham F.
The paper investigates the challenges that musicians face when playing in a paediatric hospital, drawing on case study evidence from a long-standing programme in Italy. The research focussed on identifying: (i) the inherent challenges of being a performer in a hospital; and (ii) the professional characteristics of the musicians who perform in hospitals. As part of a wider, cross-cultural study, musicians ( N = 8) were asked to report their (i) physical and (ii) psychological perceptions, before and after their musical performance in the hospital across four weeks. Interview data were analyzed according to content analysis and were informed by grounded theory. Results suggest that performing in a hospital setting is particularly demanding psychologically and emotionally where the nature of the musicians' role requires them to improvise (i) as part of their normal performance practice, seeking active collaboration by the patient, and (ii) environmentally, in relation to changes in the medical condition of their client/patient/audience. The results are also explained in terms of inherent tensions in a professional musical identity that requires expert performance in a clinical setting.